Eco-creativity generative architecture an upcycled art village and ecopark towards a culture of circularity - Alabanza, Terena Joelle S.; Gines, Leonido Jr. M. (Quezon City College of Architecture, University of the Philippines Diliman, 2024)
Waste pollution in the Philippines is the result of increasing waste production and its
mismanagement, especially in terms of materials that are not accepted by recycling
facilities. The absence of a circular system to address this has resulted in large volumes
of unrecyclable waste materials ending up in landfills, streets, and waterways. Studies
have highlighted how circularity can be achieved using waste infrastructure that
processes recyclable materials into raw materials for new products; however,
discarded materials that conventional recycling facilities cannot process remains
unaddressed. To extend the closed-loop system of recycling beyond conventional
recyclable materials, such as plastic bottles and paper, it is necessary to reimagine the
recycling system as one that also repurposes and upcycles materials, rather than merely
processing recyclable materials. However, efforts to resolve the issue of discarded
waste will only be effective if the general public’s lack of eco-consciousness is
addressed through community involvement and the democratization of waste
repurposing activities. Thus, this study explores how architecture can generate ecocreativity
to foster a culture of circularity by increasing awareness of environmental
issues and introducing creative means of repurposing material waste. This is achieved
through an upcycled art village and ecopark in Imus, Cavite, which primarily
repurposes reusable material waste into artworks and community innovations.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Upcycling (Waste, etc.) -- Imus (Cavite); Eco-creativity.; Artist village